Incorporation of resistance genes to stem and leaf rust into tue wheat cultivar iac 17 maraca - Felicio, João Carlos; Camardo, Carlos Eduardo de Oliveira; de Castro, Jairo Lopes; Ramos, Valdir Josué (Pesquisa Agropecuaria Brasileira, 1993)
Twenty-nine inbred lines obtained by crossing the IAC 17 cultivar with proved sources of resistance to Puccinia recondita (Lr genes) and Puccinia graminis tritici (Sr genes), from the wheat breeding program of the "Instituto Agronômico" were evaluated by experiments carried out at different wheat regions of the State of São Paulo, in the 1987/90 period. Grain yield, resistance to rusts and tolerance to aluminium toxicity were analysed. Considering grain yield, the inbred lines H.2301-2, 14.2301-4, H.2301-1, H.2301-3, H.2301-5, H.2302-1 and H.2297-1 presented good performance showing wide regional adaptation. Under greenhouse and field tests for Puccinia recondita it was observed that the resistance gene Lr 19 giving resistance to all races presented in Agatha was transferred to H. 2305 and the resistance gene Lr 24 for the races B25, B26, B27, B31, B32 and B33 presented in Agent was incorporated into H.2306-2 germplasm. In relalion to Puccinia graminis tritici the genotypes showed variable reactions of resistance and susceptibility to the tested races under greenhouse conditions. Under field conditions the treatments H.2306-2, H.2299-1 and H.2306-1 exhibited good resistance. The tolerance to the presence of toxic aluminium became demonstrated in H.2305, H.2302-2, H.22994 and H.2297-1 using the concentration of 6 mg/liter of this element into the nutrient solution.